2017
DOI: 10.1515/cttr-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nicotine and Nicotine-Related Compounds in Electronic Cigarette Liquids and Aerosols by Liquid Chromatography-Tandem Mass Spectrometry

Abstract: SUMMARYThe objective of this study was to develop and validate an analytical method for determining nicotine and nicotine related compounds (i.e., nicotine-N-oxide, cotinine, nornicotine, anatabine, myosmine, anabasine, and β-nicotyrine) in e-cigarette aerosols and e-liquids. Aerosol collection was achieved using a Cambridge collection pad. The sample preparation consisted of adding deuterated internal standards to the collection pad and extracting with 100 mM ammonium acetate solution using a wrist-action sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…In addition, using a methanol extraction procedure, concentrations of all alkaloids in aerosol and smoke were determined. The results of this study confirm the work of others [1,9,16,17] who indicated that NRAs in E-liquid and ECIG-generated aerosol are in substantially lower levels than in cigarettes and conventional cigarette smoke. The advantage of the methodology used in this study is that the extraction procedure for aerosol and smoke, although less efficient in terms of percent recovery, is simple (i.e., few methodological steps), clean (i.e., reduced noise and interference in the chromatographic analysis) and fast (i.e., <2 hours/sample) and HPLC-PDA can accurately measure NRAs at extremely low levels.…”
Section: Introductionsupporting
confidence: 91%
“…In addition, using a methanol extraction procedure, concentrations of all alkaloids in aerosol and smoke were determined. The results of this study confirm the work of others [1,9,16,17] who indicated that NRAs in E-liquid and ECIG-generated aerosol are in substantially lower levels than in cigarettes and conventional cigarette smoke. The advantage of the methodology used in this study is that the extraction procedure for aerosol and smoke, although less efficient in terms of percent recovery, is simple (i.e., few methodological steps), clean (i.e., reduced noise and interference in the chromatographic analysis) and fast (i.e., <2 hours/sample) and HPLC-PDA can accurately measure NRAs at extremely low levels.…”
Section: Introductionsupporting
confidence: 91%
“…Based on published literature, earlier HPLC analytical methods have been developed for analysis of nicotine from e-liquids by reversed phase chromatography using a C18 column [ 11 , 12 , 18 ]. Some references for LC-MS method also describe use of a C18 column for separation of nicotine from other ingredients in e-liquids [ 13 , 14 ]. Therefore, a C18 column was initially used for nicotine analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the addictive nature of nicotine, e-liquids need to be regulated for the total nicotine content as well as free base nicotine yield. ere are published methods for determining total nicotine content in e-liquids using gas chromatography and liquid chromatography coupled with mass detectors [27][28][29]. Recently, we have proposed a HPLC method based on peak purity criteria for accurate quantification of total nicotine content [19].…”
Section: Discussionmentioning
confidence: 99%